Studi Komparatif Konsep Keluarga Sakinah Menurut Badan Penasihat Dan Pelestarian Perkawinan Kantor Urusan Agama Kecamatan Trawas Dan Quraish Shihab - M. Ferry Abdillah; Fatkhiyatus Su'adah; Makinun Amin (CV. ITTC INDONESIA, 2025)
The results of this research BP4 KUA Kecamatan Trawas Trawas emphasized the importance of religious values, responsibility, and social support in building a harmonious family. Meanwhile, Quraish Shihab offers a more philosophical and spiritual outlook, focusing on love, the balance between this world and the afterlife, as well as the importance of psychological and emotional aspects in family relationships. Both have the same goal, which is to create a harmonious and affectionate family.However, BP4 KUA Kecamatan Trawas Trawas is more practical and structural in its approach, while Quraish Shihab emphasizes more spiritual and philosophical aspects. Although their approaches are different, they complement each other in providing guidance towards the sakinah family. The advantage of BP4 KUA Kecamatan Trawas Trawas lies in its practical and structured guidelines that are easy to apply, but may be less flexible and do not emphasize the psychological aspect enough. In contrast, Quraish Shihab offers deep spiritual insights, but his approach can be perceived as too abstract and lacks practical guidance. These two approaches, despite their weaknesses, can complement each other to achieve the goal of a balanced and harmonious sakinah family.